Economics of different alternative livelihood projects in Southern municipalities of Iloilo. - Besana, Nikkei Mesa
Poverty incidence in the Philippines is continously increasing. In line with this the government seeks for opportunities for poverty alleviation. The Food and Agriculture Organization (FAO) of the United Nations in cooperation with the University of the Philippines in the Visayas (UPV) offered different alternative livelihood projects in southern municipalities of Iloilo namely: Tigbauan (shrimp paste making), Miag-ao (salt making) and San Joaquin (fish sauce making). The study described the socio-demographic profiles of the beneficiaries of the projects along with the problems encountered during and after project implementation. The production processes were also described along with the costs of production. Revenues and profit were derived based on the existing price of the product in the market. Private cost was identified from first up to fourth liquidations. profit was calculated in every livelihood project and accounted to 728.34 Php for shrimp paste making in Tigbauan, 2,205.54 for salt making Php in Miagao and 1,570 Php for fish sauce making in San Joaquin per individual. Payback period derived was 1.07 that means the initial invesment will be recovered in no less than a year. Return on investment was 0.93, which implies that for every peso invested, 1.14 Php returns to the investment.